Associação entre ansiedade, depressão e qualidade de vida em idosos com síndrome da fragilidade e portadores de insuficiência cardíaca - MORAES, Maria Jozelia Diniz (2018)
Introduction: Elderly people represent more than 80% of patients with Heart Failure (HF). Fragility Syndrome is a distinct biological syndrome that reflects the decline of biological reserve as well as resistance to stressors. The majority of elderly patients with HF are fragile, with multiple comorbidities, among them anxiety and depression, which negatively impact the life quality of these patients. Objective: To evaluate the prevalence and relationship between frailty, anxiety, depression and health-related quality of life (HRQOL) in elderly patients with HF. Methods: A cross-sectional study was carried out to evaluate 16 patients (10 men and 06 women) with HF. Fragility was measured by the Tilburg Frailty Indicator (TFI) scale and the Edmonton Fragility Scale. The prevalence of depression was assessed by the Geriatric Depression Scale (GDS) and anxiety by the Inventory of Geriatric Anxiety. While quality of life was assessed by the Minnesota Living with Heart Failure Questionnaire (MLHFQ). The Shapiro Wilk and Kolmogorov-Smirnov tests were used to verify the normality of the continuous variables. Associations were verified by Fisher's Exact Test. The tstudent test or the Mann-Whitney test was applied to verify the comparison between individuals with or without anxiety and / or depression. Data were analyzed by statistical software Statistical Package for Social Science (SPSS), version 19.1 with an alpha significance level of maximum 5%. Fragility, depression and anxiety were present in 75%, 50% and 68% of the patients, respectively. Life quality was considered good by 62% of the patients. Conclusion: There was a high prevalence of frailty, depression and anxieties in elderly patients with heart failure. The study suggests that fragility detection should be incorporated into the assessment of patients with HF.